Analisis Pengaruh Atribut Produk, Harga, dan Word of Mouth Terhadap Keputusan pembelian Sepeda Motor Honda (Studi Kasus di Daerah Kota Pontianak) - B11111030, SYAHRONI (Jurnal Manajemen Update, 2015)
The development of economy fueled competition in all sectors, especially in any kind of business that is the same, namely competition in the motorcycle industry. Intense competition makes bussinessmen competing for increasing sales and market share to get expected profit. Therefore, companies perform a variety of ways to influence consumer purchasing decisions. In this study aimed to analyze the influence of the independent variable product attributes, price, and WOM against the dependent variable, namely the buying decision. This study uses primary data obtained from questionnaires where the sample in this study is society inÂ  Pontianak City. Analysis of data in this study using multiple linear regression analysis technique. These results indicate that the variable Product Attributes significant effect on buying Decision. While the variable price and WOM does not significantly influence the buying decision of consumers Honda motorcycle in Pontianak City. Keywords: Attributes Product, Price, WOM and Purchasing Decision.